INFLUENCE OF THE SHADOW ECONOMY ON ECONOMIC GROWTH - Mandroshchenko, Olga; Malkova, Yulee; Tkacheva, Tatyana (Journal of Applied Engineering Science, 2018)
Shadow economy is being paid a lot of attention in the world. This field of research is rather complex, specific and has a number of changeable characteristics. Therefore, the shadow economy has a number of problems to study. The scale and scope of the shadow economy are so that it is becoming the second one. Meantime, it has a great potential for an ordinary economy to grow. Therefore, it is obvious that the paper is relevant from a practical point of view. The aim is to study the influence of shadow activities on economic growth and to identify development prospects based on the analysis of the existing capacity. The authors use scientific methods of research such as empirical, historical and theoretical ones (for example, literature analysis, system analysis and research, settlement and constructive analysis, vertical and horizontal analysis). Economical and statistical methods (comparison, summary and grouping; the method of absolute and relative values, average values) are also used in the study. The authors believe that the development of the shadow economy causes both negative and positive consequences for the economy and for society itself. Therefore, they should be considered when implementing the economic policy of the country.